2016
DOI: 10.1002/slct.201601263
|View full text |Cite
|
Sign up to set email alerts
|

Order-Disorder Phase Transition, Anisotropic and Switchable Dielectric Constants Induced by Freeze of the Wheel-Like Motion in a Hexafluorosilicate-Based Crystal

Abstract: An order-disorder phase transition is found in a hexafluorosilicate-based crystal, bis(betainium) hexafluorosilicate bis (betaine) (1). At room temperature, 1 crystallizes in an orthorhombic space group Fddd and the hexafluorosilicate moiety exhibits partial disorder which originates from a uniaxial wheellike rotation. As temperature decreases, a total freeze of this wheel-like motion results in a second-order phase transition at 250 K and the low temperature phase of 1 belongs to a monoclinic space group C/2c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Novel organic-inorganic hybrid complexes have the potential of combining the distinct properties of their components and, therefore, exhibit appealing features (e.g., dielectric anisotropy, uniaxial polarity ferroelectricity, and strongly non-linear properties) and diverse structures (e.g., zero-dimensional molecular motors, one-dimensional chains, two-dimensional layers, and three-dimensional networks) [6][7][8][9][10]. From the viewpoint of crystal engineering, the assembly of molecular complexes with motional or flexible components is an effective and rational strategy [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Novel organic-inorganic hybrid complexes have the potential of combining the distinct properties of their components and, therefore, exhibit appealing features (e.g., dielectric anisotropy, uniaxial polarity ferroelectricity, and strongly non-linear properties) and diverse structures (e.g., zero-dimensional molecular motors, one-dimensional chains, two-dimensional layers, and three-dimensional networks) [6][7][8][9][10]. From the viewpoint of crystal engineering, the assembly of molecular complexes with motional or flexible components is an effective and rational strategy [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported molecular rotators based on supramolecules formed by crown ether and anilinium derivatives that showed reversible phase transitions via hydrogen bonding. For example, a layered crystal of (2-nitroanilinium)(18-crown-6)(IO 4 ) showed a pair of reversible peaks at 260.5 K (cooling) and 264.5 K (heating) with heat hysteresis of approximately 4 K. Structural analysis and potential energy calculations indicated that the dielectric anomaly and phase transition occur because of intra-and intermolecular proton transfer of -NH þ 3 in 2-nitroanilinium as a consequence of -NO 2 motion in the cation [53][54][55]. It was suggested that hydrogen-bonding interactions and/or molecular motion give rise to symmetry breaking, thus leading to the dielectric anomaly behaviour as well as the phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Recently, diverse methods were used to construct and design new hybrid molecular-based materials with high-temperature reversible phase transition. [6][7][8][9][10][11] Crown ether is a kind of a typical host molecule, and acts as a stator and then can be widely used as a building block to create supramolecular host-guest compounds, while the guests, protonated organic amine cations R-NH 3 + , are easily anchored in the cavity of crown ethers via strong hydrogen bonds. [12][13][14][15][16][17] This assembled architecture with large intermolecular and intramolecular spaces is beneficial to molecular rotation and molecular group motion of host-guest supramolecular compounds.…”
mentioning
confidence: 99%